2020
DOI: 10.1111/jace.17061
|View full text |Cite
|
Sign up to set email alerts
|

Structural and thermal behavior of 45S5 Bioglass®‐based compositions containing alumina and strontium

Abstract: The present research exposes the influence of 2 mol% of Al2O3 and 2 mol% SrO in 45S5 Bioglass®‐based compositions. Four compositions were produced to elucidate the difference in how both oxides influence structure and thermal behavior separately and their synergy when together. Thermal properties, crystallization tendency, and sintering behavior was evaluated by differential scanning calorimetry, hot stage microscopy, and dilatometry. Changes of medium‐range structures were characterized by Qn distribution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Bioactive glasses are usually formed from open silicate networks, i.e., interconnected silicate chains and rings that result in porous materials, while other silicate networks (sheets) are less porous (denser) and occur infrequently. The room-temperature Raman results obtained by deconvolution were then compared with previous research results and found to be in good agreement [34]. In the future, more experiments will be needed to investigate the changes in molecular bonds in bio glass samples at high temperatures.…”
Section: Table II Chemical Composition Of Three Testing Samples (Eaf ...mentioning
confidence: 54%
See 1 more Smart Citation
“…Bioactive glasses are usually formed from open silicate networks, i.e., interconnected silicate chains and rings that result in porous materials, while other silicate networks (sheets) are less porous (denser) and occur infrequently. The room-temperature Raman results obtained by deconvolution were then compared with previous research results and found to be in good agreement [34]. In the future, more experiments will be needed to investigate the changes in molecular bonds in bio glass samples at high temperatures.…”
Section: Table II Chemical Composition Of Three Testing Samples (Eaf ...mentioning
confidence: 54%
“…There is an overall shift of the spectral features in the Q region to a higher wavenumber when the sample is heated from room temperature to 700 • C. When the temperature exceeds the sample's melting point at 1300 • C, the Q region changes significantly in the range of 950-1050 cm −1 . To further understand the relationship between chemical bonds and the Raman spectra of bio glass, the Raman spectra at room and high temperatures were deconvoluted, applying peaks identified from an earlier study on the bio glass [34]. Seven major Raman peaks were deconvoluted, and the attributions considered for the peak fitting were as follows: Q 0 at 864 cm −1 ; Q 1 at 906 cm −1 ; Q 2 at 944 cm −1 ; P-O-P stretching at 974 cm −1 ; O-P-O-stretching of the P 2 O 5 sheet unit at 1008 cm −1 ; asymmetric stretching of the bridge oxygen in all Q species; and the symmetric stretching of Q 3 at 1086 cm −1 , as shown in Fig.…”
Section: Table II Chemical Composition Of Three Testing Samples (Eaf ...mentioning
confidence: 99%
“…Moreover, an additional broad peak at 780–890 cm −1 is observed for the modified bioglass. The deconvoluted Raman spectra ( Figure 4 ), show that this peak could be distinguished as three different bands located at 782–804 cm −1 , 806–829 cm −1 , and 857–886 cm −1 , which are assigned to vibrations of NbO 6 octahedrons with different degrees of distortion, to the vibration of NbO 4 units, and to the symmetric stretching of Q 0 units in the silicate network (SiO 4 4− ), respectively [ 63 , 64 , 65 ]. The vibrational bands of NbO 6 units increased with increasing Nb 2 O 5 concentration up to 2 mol%, whereas the NbO 4 vibrational band decreased.…”
Section: Resultsmentioning
confidence: 99%
“…BGs are amorphous in origin and have intermediate oxides, network modifiers, and network formers, in their framework [120]. Without external materials, the network designers could shape glasses independently [121].…”
Section: Bioactive Glass Drug Carriersmentioning
confidence: 99%